Nanofibre toughening of dissimilar interfaces in composites. (October 2020) - Meireman, Timo; Daelemans, Lode; Van Verre, Elisa; Van Paepegem, Wim; De Clerck, Karen
Abstract: Fibre reinforced composite laminates are key engineering materials allowing to design lightweight components with high mechanical properties. Yet they are prone to delamination between the reinforcing plies, which in turn limits the damage resistance of many applications. This is especially true for the interfaces between dissimilar reinforcing plies that are often encountered in actual components, e.g. differences in fibre orientation, fibre material or ply architecture, where high interlaminar stresses can occur. Nanofibrous toughening veils are known to increase the damage resistance when inserted between similar reinforcing plies, but it is currently unknown how they perform when delamination occurs at dissimilar interfaces. Here, the nanofibre toughening of frequently encountered dissimilar interfaces such as occurring between multidirectionally stacked unidirectional fibre plies (+45°/−45°), multistructural stackings (unidirectional versus fabrics) and multimaterial configurations (glass fibres versus carbon fibres) are analysed. These interfaces largely exert their influence on the crack path during delamination and thus alter the effectiveness of nanofibre toughening. Poly(ether- block -amide) nanofibres of the biosourced polyamide 11 family result in a large increase in mode I and mode II interlaminar fracture toughness for all the tested dissimilar interfaces. We show that their effectiveness however depends on the underlying delamination mechanics present in different dissimilar interfaces. Graphical abstract: Unlabelled Image Highlights: For the first time, the delamination resistance of diverse dissimilar interfaces is highly increased by nanofibre toughening. An extensive mode I and II increase of respectively 30–50% and 70–130% was achieved for each considered dissimilar interface. The crack path repeatedly crosses the nanofibre toughened zone which largely contributes to the increased fracture toughness. Crack bifurcations develop towards adjacent interfaces due to the improved toughness of nanotoughened dissimilar interfaces.